Говорящие имена собственные в саге о „Гарри Поттере” в переводе на русский и польский языки - Rachut, Konrad (Studia Rossica Posnaniensia, 2015)
In the process of literary communication between the author and the readers, the translator plays the role of a linguacultural mediator. Since each proper name is usually deeply rooted in the original cultural system, the translator is forced to retain its core meaning and leave aside its secondary aspects. Therefore, as the understanding of particular literary worlds depends on the respective onomastic structures, translations seem to be partial interpretations of original texts.